Analysis of the Use of Instagram as a Promotional Media for Sumbawa University of Technology in Attracting the Interest of Prospective Students from Various Regions - Rafika Nirfanasari (Takaza Innovatix Labs Ltd., 2026)
The use of social media has now become a marketing strategy in the field of education, especially universities in Indonesia, such as Instagram which is now used by the University of Technology Sumbawa in promoting its programs to prospective students. Its use is certainly inseparable from the community's habit of obtaining information through social media, because it is considered quite effective and relevant to the current development of communication technology among the public. Instagram is one of the media used by UTS in the promotional process because of its wide reach and has quite complete features compared to other social media. This study was conducted to analyze how the use of Instagram as a medium used by the University of Technology Sumbawa to attract the interest of prospective students from various regions. The method used in this study is a descriptive method with a qualitative approach. The theory used in this study uses the theory of personal branding by Tom Peters. Research data were collected through observations and interviews with the UTS public relations team and UTS students from outside the island of Sumbawa. The results of the study show that the use of Instagram by UTS has increased significantly as seen from the increase in UTS Instagram followers in the last two years, audience interaction with the fairly active account management team, an increase in the registration information diagram and a fairly high increase in engagement rates in several UTS posts on Instagram. So it can be concluded that the use of Instagram as a campus promotional media has been utilized well by UTS and is in accordance with the theory used in this study.